2018
DOI: 10.1002/aelm.201800006
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Oxidation of Hf–Nb Alloys as a Valuable Route to Prepare Mixed Oxides of Tailored Dielectric Properties

Abstract: Metal oxides with high dielectric constant are extensively studied in the frame of substituting SiO2 as gate dielectric in nanoelectronic devices. Here, high‐k mixed HfO2/Nb2O5 oxides are prepared by a facile electrochemical route starting from sputtering‐deposited Hf–Nb alloys with several compositions. Transmission electron microscopy, grazing incidence X‐ray diffraction, and glow discharge optical emission spectroscopy are employed to study the oxide structures, disclosing a crystalline–amorphous transition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Band gap modeling of simple and complex oxides is of paramount importance for the application of such materials in numerous and important applications pertaining to different fields such as solar energy conversion (photoelectrochemical and photovoltaic solar cells, photocatalysis, and electrocatalysis), microelectronics (high- k , high-band-gap materials and resistive random access memory (ReRAM)), and active and passive anticorrosive coatings. Owing to this, the band structure calculation of solids and, notably, of oxides has been one of the most investigated subjects of materials science in the past 20 years or more . In spite of the rewarding achievements obtained in computing numerous solid-state properties of different materials, the prediction of band gap values of materials is still a formidable task also for the most advanced quantum mechanical methods rooted on density functional theory (DFT). , …”
Section: Introductionmentioning
confidence: 99%
“…Band gap modeling of simple and complex oxides is of paramount importance for the application of such materials in numerous and important applications pertaining to different fields such as solar energy conversion (photoelectrochemical and photovoltaic solar cells, photocatalysis, and electrocatalysis), microelectronics (high- k , high-band-gap materials and resistive random access memory (ReRAM)), and active and passive anticorrosive coatings. Owing to this, the band structure calculation of solids and, notably, of oxides has been one of the most investigated subjects of materials science in the past 20 years or more . In spite of the rewarding achievements obtained in computing numerous solid-state properties of different materials, the prediction of band gap values of materials is still a formidable task also for the most advanced quantum mechanical methods rooted on density functional theory (DFT). , …”
Section: Introductionmentioning
confidence: 99%
“…This is due to the barrier nature of the anodic film grown for 100 s, and the use of the EEC, as shown in Figure 4 a, is in agreement with that reported in the literature, for which the electrochemical behavior of barrier-like anodic films can be successfully modelled by a simple parallel RQ . 26 28 Conversely, in the case of AZ31 samples anodized for longer times (e.g., 30 and 60 min), a more complex EEC is needed to model the electrochemical behavior of anodic films immersed in HS. In particular, the EEC used is shown in Figure 4 b, where the parallel ( R b Q b ) is in series with R p representing the outer layer resistance, that is, the electrolyte resistance inside the pores of the anodic films.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with chemical oxidation, electrochemical oxidation only requires dialysis to purify CQDs. The electrochemical oxidation of impurities can change the oxidation state by applying an external voltage or releasing chemistry to transfer electrons between mole-cules or ions [33]. Zhou et al reported that CQDs with many oxygen-containing functional groups were prepared by cyclic voltammetry using multi-walled carbon nanotubes as working electrode [34].…”
Section: Carbon Quantum Dots (Cqds)mentioning
confidence: 99%
“…Compared with chemical oxidation, electrochemical oxidation only requires dialysis to purify CQDs. The electrochemical oxidation of impurities can change the oxidation state by applying an external voltage or releasing chemistry to transfer electrons between molecules or ions [33]. Zhou et al.…”
Section: Synthesis Of Carbon‐based Quantum Dotsmentioning
confidence: 99%